2020
DOI: 10.1002/jbmr.4455
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Trigger Disturbed Bone Healing in Osteoporotic Mice

Abstract: Mast cells are important tissue-resident sensor and effector immune cells but also play a major role in osteoporosis development. Mast cells are increased in numbers in the bone marrow of postmenopausal osteoporotic patients, and mast cell-deficient mice are protected from ovariectomy (OVX)-induced bone loss. In this study, we showed that mast cell-deficient Mcpt5-Cre R-DTA mice were protected from OVX-induced disturbed fracture healing, indicating a critical role for mast cells in the pathomechanisms of impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 93 publications
4
29
0
3
Order By: Relevance
“…However, nothing is known about their involvement in trauma-induced compromised bone repair, which is frequently observed in multiply injured patients ( 2 ). Thereby, we focused on the early inflammatory phase, which is strongly affected by the additional trauma, and on the later repair phase, which serves as a read-out for successful fracture healing, and where mast cells were already shown to play an important role during fracture repair ( 26 , 29 ). In agreement with previous experimental studies ( 7 , 11 , 13 , 17 , 26 , 39 42 ), the model of combined fracture and thoracic trauma used in the present study induced an increased systemic inflammation after 3 h in mast cell-competent mice as indicated by elevated serum IL-6, CXCL-10, MCP-3, IL-5 and eotaxin levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, nothing is known about their involvement in trauma-induced compromised bone repair, which is frequently observed in multiply injured patients ( 2 ). Thereby, we focused on the early inflammatory phase, which is strongly affected by the additional trauma, and on the later repair phase, which serves as a read-out for successful fracture healing, and where mast cells were already shown to play an important role during fracture repair ( 26 , 29 ). In agreement with previous experimental studies ( 7 , 11 , 13 , 17 , 26 , 39 42 ), the model of combined fracture and thoracic trauma used in the present study induced an increased systemic inflammation after 3 h in mast cell-competent mice as indicated by elevated serum IL-6, CXCL-10, MCP-3, IL-5 and eotaxin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mast cell-deficient mice displayed diminished IL-6 levels and improved coronary inflammation in response to stress-induced trauma ( 56 ). In addition, systemic inflammatory mediator levels, including IL-6 and CXCL-10, were reduced in mast cell-deficient mice during regular and ovariectomy-induced compromised bone repair, indicating that mast cells contribute to fracture-induced inflammation ( 26 , 29 ). Mast cell stabilization using cromolyn in mice improved the outcome of ischemic-reperfusion injury associated with reduced blood IL-6 and TNF levels ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that female mice lacking mast cell chymase Mcpt4 showed higher serum bone anabolic markers and a higher periosteal bone formation rate 60 suggesting the functional effect of mast cell chymase on bone health. Recently, a study was reported by Fischer et al 61 in a MCs deficient Mcpt5-Cre-R-DTA mice model where deficiency of MCs protected mice from Ovx-induced osteoporosis and perturbed fracture healing, indicating a crucial role of MCs in the pathophysiology of osteoporosis under estrogen-deficient conditions. In wild-type conditions, MCs triggered fracture provoked an inflammatory response by promoting release of inflammatory molecules IL-6, CXCL10, and midkine (Mdk) along with inducing the infiltration of neutrophils at the fracture site in ovariectomized mice.…”
Section: Innate Immune Cells and Osteoporosismentioning
confidence: 93%
“…In wild-type conditions, MCs triggered fracture provoked an inflammatory response by promoting release of inflammatory molecules IL-6, CXCL10, and midkine (Mdk) along with inducing the infiltration of neutrophils at the fracture site in ovariectomized mice. 61 IL-31, secreted by MCs, are also being employed as biomarker to monitor disease severity in various allergic diseases. Interestingly, a study reported that increased levels of IL-31 in post-menopausal osteoporotic patients are correlated with reduced BMD.…”
Section: Innate Immune Cells and Osteoporosismentioning
confidence: 99%